Halal herbal products integrity risk through supply chain: a conceptual study - Rajendran, Salini Devi; Kamarulzaman, Nitty Hirawaty (Institut Penyelidikan Perhutanan Malaysia, 2015)
There are thousands of herbal products and supplements available in the market as a nutritional boost particularly for families who strive to maintain a healthy, halal lifestyle. An increased awareness on the breadth of herbal labelled as halal is crucial, as consumers globally strive for halal consumption. The length and complexity of herbal supply chains raise questions on the authenticity of herbal products labelled as halal and halal integrity of the supply chain. The risks involved in ensuring product integrity as it moves through multiple tiers of suppliers, further aggravates the uncertainty. Thus, it is very challenging for the manufacturers to reduce risks and maintain the integrity of halal herbal products. As the halal market is huge, demand for halal herbal products is expected to grow bigger in the future, thus the risks must be given serious attention to maintain the integrity of halal herbal products in providing halalan toyyiban products for the needs and well-being of the consumers. Thus, this conceptual paper will investigate the risks in halal herbal products supply chain. A quantitative study will be carried out to obtain information from supply chain players including herbal-based manufacturers listed by FRIM and JAKIM. Data will be analysed using descriptive statistics, regression analysis, chi-square test, factor analysis, correlation analysis and CFA. The results are expected to reveal that halal integrity risk such as production risk, raw materials risk, food security risk, outsourcing practices risk, service risk, and logistics risks influence halal integrity along the herbal supply chain.